Association between internet addiction and loneliness across the world: A meta-analysis and systematic review - Hossein Mozafar Saadati; Hossein Mirzaei; Batool Okhovat; Farzad Khodamoradi (Elsevier, 2021)
There might be an association between Internet addiction (IA) and loneliness; however, inconsistent evidence suggests that the severity of this association remains unclear. This study was conducted to assess the association between IA and loneliness. A systematic literature search was conducted in four online databases, including PubMed (MESH terms), Web of Science, Scopus, and Embase. Observational studies measuring the association between IA and loneliness were screened and included in this review. A meta-analysis was conducted using the Stata software. Twenty-six articles with a total sample size of 16496 subjects were included in the analysis. A moderate positive association (r = 0.15 (95% CI: 0.13, 0.16)) was found between IA and loneliness. The individuals with IA had significantly higher scores of loneliness. According to this meta-analysis, we need more attention to the early symptoms of loneliness in individuals with IA. Longitudinal studies are needed to determine the temporality of this association considering adjustment for time varying confounders.